Performance evaluation of two interconnected high voltage utility substations using PRP topology based on IEC 62439-3 - Kumar, S.; Das, Narottam; Islam, Syed (IEEE, 2018)
© 2017 IEEE. In a modern power system network having multiple interconnected High Voltage (HV) substations, communication amongst Intelligent Electronic Devices (IED) becomes an important feature in an automation system. Time critical information, such as feeder faults, overcurrent, under frequency messages between multiple geographically isolated substations have opened up number of issues related to reliability in protection, automation and control. There are problems related to latency, data loss and transfer of Sampled Value (SV) packets transmitted to these inter-connected substations on radio wireless and Ethernet mode linked up in a Wide Area Network (WAN) configuration. Few other key area of concerns in a digital protection scheme are packet losses, errors in packet arrival at destination, latency in transmission, End to End delay in packet transfer due to flooding of the network, out of sequence packet arrival etc. Error prone packets could seriously compromise the protection scheme and endanger the safety of primary plant assets in a transmission substation. This paper investigates performance of SV packet transmission between two interconnected substations]. Practical simulations were performed to evaluate the performance of SV packets in a laboratory set up to assess the performance of digital protection scheme based on Parallel Redundancy Protocol (PRP) topology involving digital equipment such as Merger Units (MUs), switches, IEDs and Redundant boxes (Red box), etc.